2020
DOI: 10.3390/molecules25153454
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance Spectroscopy for Non-Destructive Measurement and Genetic Analysis of Amounts and Types of Epicuticular Waxes on Onion Leaves

Abstract: Epicuticular waxes on the surface of plant leaves are important for the tolerance to abiotic stresses and plant–parasite interactions. In the onion (Allium cepa L.), the variation for the amounts and types of epicuticular waxes is significantly associated with less feeding damage by the insect Thrips tabaci (thrips). Epicuticular wax profiles are measured using used gas chromatography mass spectrometry (GCMS), which is a labor intensive and relatively expensive approach. Biochemical spectroscopy is a non-destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…As with with other aggressive forest diseases, it is necessary to detect infected individuals, understand how the pathogen affects the host, and then identify resistant individuals. The potential of using remote sensing to screen for resistant individuals has been demonstrated in both agricultural and forest systems [16,20,34,36]. Here, we demonstrate that resistance in M. polymorpha to C. lukuohia is detectable using VSWIR spectroscopy.…”
Section: Plos Onementioning
confidence: 59%
See 2 more Smart Citations
“…As with with other aggressive forest diseases, it is necessary to detect infected individuals, understand how the pathogen affects the host, and then identify resistant individuals. The potential of using remote sensing to screen for resistant individuals has been demonstrated in both agricultural and forest systems [16,20,34,36]. Here, we demonstrate that resistance in M. polymorpha to C. lukuohia is detectable using VSWIR spectroscopy.…”
Section: Plos Onementioning
confidence: 59%
“…This, in turn, has resulted in heritable differences in reflectance spectra of M. polymorpha across environmental gradients [70]. Disease resistance screening using spectroscopy is in early stages of development, but this technique has been demonstrated to successfully distinguish between resistant and susceptible hosts in a number of forest and agricultural plant species [16,20,34,36]. This study demonstrates that a resistance signal to C. lukuohia infection is present in leaf reflectance data, but because of the influence of site and genetic factors on leaf spectra, it is important to continue considering these factors in future investigations.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that onions with waxy leaves suffer more thrips damage compared to onions with semi-glossy and glossy leaves, since their leaves accumulate only intermediate or sparse amounts of epicuticular waxes and have lighter green colors that result in slower thrips population growth and reduced egg hatching [8,14,[16][17][18][19]. Lower wax phenotypes can be conditioned by a single recessive locus (gl), such as the single recessive locus (gl wp ) found in the glossy phenotype White Persian, which has been mapped to chromosome 8 and been shown to interact with a region of chromosome 1 that acts to increase waxy progeny numbers [20][21][22][23]. Relative to other epicuticular waxes, the amount of hentriacontanone-16 wax may also influence the total amount of leaf wax [24].…”
Section: Introductionmentioning
confidence: 99%
“…The onion cultivar Odourless Green Leaf (OGL) has a light green leaf color, is less attractive to thrips relative to waxy onion (Cramer et al, 2014), and has a unique profile of epicuticular waxes (Munaiz et al, 2020b). During this research, we determined the genetic basis of the wax profile and glossy phenotype of OGL, and we showed that it is inherited independently from the gl wp locus (Munaiz and Havey, 2020).…”
mentioning
confidence: 99%